Analisis Komponen Penyusun Desain Kegiatan Laboratorium Berbasis Keterampilan Proses Sains Pada Materi Kerja Enzim Katalase: (Analysis of the components Designing Laboratory Activities based on science process skills of the Working of Catalyst Enzyme) - Laurina Sinurat; Bambang Supriatno; Sri Anggraeni (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
One of the objectives of learning biology is to give students experience in the scientific method which is the demand of the 21st century. This ability is a science process skill that can be obtained in laboratory activities. So that the design of laboratory activities should lead to science process skills. This study aims to analyze the design of laboratory activities to find out: 1) the relevance of competence and content to basic competencies, 2) what competencies or abilities are built in the practicum, 3) tools, materials according to school standards and work procedures are well structured or not. , 4) the knowledge gained whether the focus is on the main thing or not. This study uses a qualitative descriptive method with the ANCOR stages, namely analysis, testing and reconstruction of five designs of laboratory activities on the working material of the catalase enzyme. The results of the study indicate that the lack of competence in science process skills built on the five designs of laboratory activities is proven based on the results of the analysis on the acquisition of knowledge is still lacking. Therefore, knowledge reconstruction needs to be carried out on the design of laboratory activities to improve the quality of laboratory activities in accordance with the demands of basic competencies. Abstrak. Salah satu tujuan pembelajaran biologi yaitu memberi pengalaman kepada siswa pada metode ilmiah yang merupakan tuntutan abad 21. Kemampuan tersebut merupakan keterampilan proses sains yang bisa didapatkan dalam kegiatan laboratorium. Sehingga desain kegiatan laboratorium sebaiknya mengarah kepada keterampilan proses sains. penelitian ini bertujuan untuk menganalisis desain kegiatan laboratorium untuk mengetahui : 1) relevansi kompetensi dan konten terhadap kompetensi dasar, 2) kompetensi atau kemampuan yang seperti apa yang dibangun dalam praktikum, 3) alat, bahan sesuai standar sekolah serta prosedur kerja terstruktur dengan baik atau tidak, 4) pengetahuan yang diperoleh apakah fokus kepada hal utama atau tidak. Penelitian ini menggunakan metode deskriptif kualitatif dengan tahapan ANCOR yaitu analisis, uji coba dan rekonstruksi lima desain kegiatan laboratorium pada materi kerja enzim katalase. Hasil dari penelitian menunjukkan bahwa kurangnya kompetensi keterampilan proses sains yang dibangun pada kelima desain kegiatan laboratorium dibuktikan berdasar hasil analisis pada perolehan pengetahuan masih kurang. Oleh karena itu rekonstruksi pengetahuan perlu dilakukan pada desain kegiatan laboratorium untuk meningkatkan kualitas kegiatan laboratorium yang sesuai dengan tuntutan kompetensi dasar.